2021
DOI: 10.1097/ccm.0000000000005026
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardiac Injury in Coronavirus Disease 2019 and Other Viral Infections—A Systematic Review and Meta-Analysis

Abstract: OBJECTIVES: Severe acute respiratory syndrome–related coronavirus-2 binds and inhibits angiotensin-converting enzyme-2. The frequency of acute cardiac injury in patients with coronavirus disease 2019 is unknown. The objective was to compare the rates of cardiac injury by angiotensin-converting enzyme-2–binding viruses from viruses that do not bind to angiotensin-converting enzyme-2. DATA SOURCES: We performed a systematic review of coronavirus disease 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Among them, PCT and CRP are two inflammatory marker proteins that have been studied deeply [ 15 ]. And, in recent years, HBP has also been gradually used in the diagnosis of bacterial infections [ 16 ].…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Among them, PCT and CRP are two inflammatory marker proteins that have been studied deeply [ 15 ]. And, in recent years, HBP has also been gradually used in the diagnosis of bacterial infections [ 16 ].…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…In contrast to the paucity of data regarding lymphocytic myocarditis in COVID-19, there is a significant proportion of autopsy [127] and EMB [128] specimens displaying an increased interstitial macrophage infiltration of the myocardium. Such high levels of myocardial macrophages point to non-specific myocardial inflammation resulting from high systemic levels of cytokines instead of direct viral-mediated myocarditis [127,129], as reported in other forms of pneumonias, although the occurrence of myocardial injury appears significantly higher in COVID than non-COVID pneumonia [120].…”
Section: Myocardial Inflammationmentioning
confidence: 72%
“…In several cohort studies from China, myocardial injury, as defined by elevated values of serum TnI, was reported in 7-28% of patients and was significantly associated with severe forms of the disease, the levels of inflammatory biomarkers, and mortality [38,116,117]. An elevation of cardiac biomarkers, including TnI and natriuretic peptides, has been reported in numerous cohort studies, with a prevalence reaching up to 50%, most notably in ICU-hospitalized patients [118][119][120] and with considerable prognostic value (OR for mortality 6.64, p = 0.03), according to a recent meta-analysis [121].…”
Section: Reduction Of Right Ventricular Contractility Evidence Of Myocardial Injury In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial injury can occur via ischemic and non-ischemic mechanisms and the overall rate of acute cardiac injury in older studies has been reported to be between 7.2 and 36%, with rates as high as 59% in those who died (18,43,44). The rate of acute cardiac injury has been found to be higher in the case of infection with viruses, such as SARS-CoV-2, that bind the ACE2 receptor, than in those with viruses that do not (45). Cardiac injury can occur early or later in the course of COVID-19 infection and recurrent episodes of cardiac injury may occur, with the latter events being associated with worse outcome (46).…”
Section: Acute Myocardial Injurymentioning
confidence: 99%